Differential early response of monocyte/macrophage subsets to intra-operative corticosteroid administration in lung transplantation - Glorion, Matthieu; Pascale, Florentina; Huriet, Maxime; Estephan, Jérôme; Gouin, Carla; Urien, Céline; Bourge, Mickael; Egidy, Giorgia; Richard, Christophe; Gelin, Valérie; De Wolf, Julien; Le Guen, Morgan; et al. (Frontiers in Immunology, 2023)
Introduction Lung transplantation often results in primary and/or chronic dysfunctions that are related to early perioperative innate allo-responses where myeloid subsets play a major role. Corticosteroids are administered upon surgery as a standard-of-care but their action on the different myeloid cell subsets in that context is not known. Methods To address this issue, we used a cross-circulatory platform perfusing an extracorporeal lung coupled to cell mapping in the pig model, that enabled us to study the recruited cells in the allogeneic lung over 10 hours. Results Myeloid cells, i.e. granulocytes and monocytic cells including classical CD14pos and non-classical/intermediate CD16pos cells, were the dominantly recruited subsets, with the latter upregulating the membrane expression of MHC class II and CD80/86 molecules. Whereas corticosteroids did not reduce the different cell subset recruitment, they potently dampened the MHC class II and CD80/86 expression on monocytic cells and not on alveolar macrophages. Besides, corticosteroids induced a temporary and partial anti-inflammatory gene profile depending on cytokines and monocyte/macrophage subsets. Discussion This work documents the baseline effects of the standard-of-care corticosteroid treatment for early innate allo-responses. These insights will enable further optimization and improvement of lung transplantation outcomes.